Resiliencia e impulsividad en agentes civiles de transito del Gobierno Autónomo Descentralizado del cantón Riobamba, 2021 - Aucancela Carguachi, Verónica Estefanía, Armas Zavala, Lisbeth Jaqueline (2021)
ABSTRACT The research project was carried out in the Directorate of Mobility, Transit, and Transport of the GAD of Riobamba. Resilience allows the individual to adapt to life situations, while impulsivity tends to present quick and unexpected reactions to stimuli. The objective was to evaluate the resilience and impulsivity of the Civil Traffic Officers in the year 2021. Regarding the quantitative approach of the non-experimental field, it was of cross-sectional design and descriptive level; The population was made up of 124 male and female officers, aged between 21 and 28 years, with a = 24 and σ = ± 1,871. For obtaining data, the Resilience Scale of Wagnild and Young (1993) and the Impulsivity Scale of Barratt (1983) adapted version Bis- 11 were used. The results indicated that the level of resilience in the study population is high with 77.4%, and there is a lower level of impulsivity represented by 99.2% of the officers. It was determined that cognitive impulsivity prevails with a value of = 1.5081 and σ = ± 0.42464. The results made it possible to develop a psychoeducational program on "Resilience and impulsivity." In conclusion, the studied population has a high level of resilience and presents a low level of impulsivity, which predominates in the officers' cognitive; this suggests that they would present difficulties in tasks that demand attention for prolonged periods and tend to make decisions quickly. Keywords: resilience, impulsive behavior, civil traffic officers. Reviewed by: Mgs. Hugo Romero ENGLISH PROFESSOR c.c. 0603156258